Pragmatism and mixed method (Research, Society and Development, 2020)
The aim of this study was to reflect on pragmatism in the philosophers' strands Charles Sanders Peirce, William James and John Dewey as a philosophical reference of the mixed method of Creswell & Clark. Pragmatism as a worldview arose from actions, situations and consequences, rather than antecedent conditions (as in post-positivism), having a concern with applications (what works) and solutions to problems. The researchers emphasized the problems and used all available approaches to understand the problem, instead of focusing on the method, being free to choose research methods, techniques and procedures that best suited their needs and purposes, which was consistent with the mixed method. , which combined a qualitative and quantitative method, enabling the complementation of the collected and analyzed data, in order to obtain more comprehensive information in relation to the research question, allowing to break the methodological limitations of these approaches. From the reflection it was possible to conclude that the mixed method of multiple methods, different worldviews, and varied assumptions, as well as different forms of data collection and analysis, is philosophically connected to pragmatism.